2014
DOI: 10.1186/1475-2891-13-13
|View full text |Cite
|
Sign up to set email alerts
|

Is drop-out from obesity treatment a predictable and preventable event?

Abstract: BackgroundAttrition is an important but understudied issue that plays a vital role in the successful treatment of obesity. To date, most studies focusing on attrition rates and/or its predictors have been based on pretreatment data routinely collected for other purposes. Our study specifically aims at identifying the predictors of drop-out focusing on empirically or theoretically-based factors.MethodsWe conducted a retrospective observational study in an academic outpatient clinical nutrition service in Pavia,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
73
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(82 citation statements)
references
References 33 publications
8
73
0
1
Order By: Relevance
“…The most prominent predictors of adherence identified were: early weight loss success , lower baseline BMI , better baseline mood , being male and older age .…”
Section: Discussionmentioning
confidence: 99%
“…The most prominent predictors of adherence identified were: early weight loss success , lower baseline BMI , better baseline mood , being male and older age .…”
Section: Discussionmentioning
confidence: 99%
“…Another notable highlight was the high percentage of African American (79%) participants, a group that is commonly underrepresented in clinical studies. Moreover, the prior studies that included subjects of African descent were generally observational, employing food-frequency questionnaires rather than a randomized intervention clinical trial (39). Unfortunately, the group samples were too small for a race-specific analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that community-based participatory research (CBPR) approaches lead to increased recruitment and retention rates. [11][12][13][14][15] In fact, use of CBPR approaches to promote health is recognized as a critical strategy in addressing health inequities among socially disadvantaged and Predictors of retention among african americans in a randomized controlled trial to test the healthy eating and active living in the sPirit (heals) intervention Oluwole A. Babatunde, MPH 1,3 ; Swann Arp Adams,PhD [1][2][3] ; Michael D. Wirth, PhD 1,3,4 ; Jan M. Eberth,PhD 1,3 ; Jameson Sofge, MPH 1,3 ; Seul Ki Choi, PhD 3,5 ; Brook E. Harmon,PhD 3,6 ; Lisa Davis, MS 3 ; Ruby Drayton, MS 3 ; Thomas G. Hurley, MS 3 ; Heather M. Brandt, PhD 3,5 ; Cheryl A. Armstead,PhD 3,7 ; James R. Hébert, ScD 1,3,4,8 Introduction: Retention of racial/ethnic minority groups into research trials is necessary to fully understand and address health disparities. This study was conducted to identify participants' characteristics associated with retention of African Americans (AAs) in a randomized controlled trial (RCT) of a behavioral intervention.…”
Section: Introductionmentioning
confidence: 99%
“…This attrition rate ranges from 10% to 80% depending on the study population, study period, and the intervention. [7][8][9][10] Factors that have been identified by previous research studies as contributing to retention of AAs in randomized controlled trials (RCT) should be incorporated into study design and approaches. Previous studies showed that community-based participatory research (CBPR) approaches lead to increased recruitment and retention rates.…”
Section: Introductionmentioning
confidence: 99%